Reliability of cable downswing load-velocity performance in golf swings. Issue 2 (17th February 2021) - Schofield, Michael; Cronin, John B.; Macadam, Paul; Storey, Adam
ABSTRACT: The cable-pulley downswing is a movement similar to the golf downswing, and therefore may offer a valuable golf specific rotational diagnostic and training tool. However, to be of value, measurements need to be stable across testing occasions. Therefore, the aim of this study was to quantify the test-retest reliability of the cable downswing across a spectrum of load-velocities. Ten male participants (21.7 ± 3.0 years, 84.6 ± 9.8 kg, 1.80 ± 0.05 m) volunteered to participate over 3 testing sessions' separated by a minimum of 3 days. Participants performed maximal velocity cable downswings across eight loads (1.25–18.75 kg), which were incrementally increased by 2.5 kg. Vertical cable stack velocity was collected at 50 Hz via a GymAware linear position transducer. Downswing velocity across all eight loads was observed to be extremely reliable (change in mean = −5.1% to 2.9%, coefficient of variation = 1.5–6.4% and intra-class correlation = 0.70–0.98), with reliability increasing with increasing trials. In conclusion, the cable downswing is a reliable method of tracking rotational ability similar to the golf downswing. Practitioners should establish an upper load relative to the apparatus and participant. Future research should determine the utility and sensitivity of this measure.